Phenotypic and functional characterization of neutrophils and monocytes from patients with myelodysplastic syndrome by flow cytometry - Schmidt, Cornelia Sabine; Nolte, Florian (Cellular immunology, 2016)
Myelodysplastic syndrome (MDS) is a clonal stem cell disorder frequently associated with inefficient granulopoiesis showing dysplastic polymorphonuclear neutrophils (PMNs). To assess PMN functionality in MDS in a clinical routine setting, 30 MDS patients and ten healthy volunteers were analyzed for PMN and monocyte phenotype and function (degranulation, CD62L shedding, oxidative burst and phagocytosis) upon stimulation with lipopolysaccharide by multi-color flow cytometry (MCFC). Our data show a heterogeneous pattern for CD66, CD16 and CD64 expression on PMNs of MDS patients. CD62L shedding rate and CD66 degranulation were reduced. Interestingly, we detected correlations between the WHO adapted prognostic scoring system (WPSS) and CD16 expression on PMNs as well as the international prognostic scoring system (IPSS) and CD11b degranulation by MCFC, suggesting clinical relevance of MCFC based function testing. In conclusion, MCFC of myelodysplastic immunophenotypes and PMN functionality are applicable in clinical settings, but further prospective studies are needed to assess the practical clinical value of such analyses.